(untitled) (Bangladesh Journal of Microbiology, 2016)
Arsenic (As) pollution in both soil and water is a global threat and challenge to us. Soil As contamination resulted in desolation of agricultural land and damaging human health via the food chain. Plant growth promoting bacteria (PGPB) enhance the ability of heavy metal/metalloid tolerance, increase biomass production in plant under adverse condition and also reduce the soil toxicity. This present study focuses on selection of the plant growth promoting trait within arsenite resistant bacteria, previously isolated from As contaminated soils of Faridpur district, Bangladesh. A total of 17 arsenite resistant bacteria belonging to 8 different genotypes comprising 6 different genera (Bacillus, Pseudomonas, Delftia, Wohlfahrtiimonas, Dietzia and Brevibacillus) were screened for their ability to produce plant growth promoting abilities such as indole acetic acid (IAA) production and phosphate solubilization (PS). Among 17 isolates, 15 93.75% (15/16) isolates produced IAA and 83.71% (12/14) isolates had the capacity to solubilize phosphate. Arsenite resistant Bacillus spp. were highly potent in both IAA production (33.33%) and phosphate solubilization (50%) followed by Pseudomonas spp. (40% IAA and 33.33% PS). High IAA production (91.5?g/ml) was exhibited by isolate Bacillus sp. A1b possessing a MICarsenite of 10 mM and maximum phosphate solubilization was observed by Bacillus sp. H2k. One of the arsenite resistant bacteria Detzia sp. H2f having 27 mM arsenite tolerance were able to produce IAA and showed maximum PS ability that was not previously reported. These isolates can be potential candidates for the enhancement of plant growth, provide protection of plants against As toxicity and be beneficial for sustainable agronomic production in As contaminated soils. Bangladesh J Microbiol, Volume 32, Number 1-2,June-Dec 2015, pp 25-31